A prospective study on early PET/CT scans during the first cycle of salvage chemotherapy for relapsed or refractory diffuse large B-cell lymphoma. Issue 1 (2nd January 2022) - Cherng, Hua-Jay J.; Chuang, Hubert H.; Steiner, Raphael; Fayad, Luis; Strati, Paolo; Nair, Ranjit; Hagemeister, Fredrick; Nastoupil, Loretta J.; Lee, Hun Ju; Neelapu, Sattva S.; Flowers, Christopher R.; Samaniego, Felipe; et al.
Abstract: Many patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL) will not respond to platinum-containing salvage chemotherapy. Predicting treatment failure earlier could help clinicians minimize chemotherapy toxicities for non-responders in favor of other treatments. We conducted a pilot study where 2 early PET/CTs were obtained on days 4 (D4) and 21 (D21) of cycle 1 (C1) of salvage therapy for DLBCL. Twenty-five patients were enrolled and have evaluable data. Ten (40%) had an unplanned therapy change after C1 and before end-of-treatment (EOT) evaluation due to treatment failure on early PET/CT as interpreted by the treating physician. Early PET/CT response at D4 or D21 was not associated with EOT response in evaluable patients. Disease specific survival was longer for patients with a persistent response on both D4 and D21 ( p = 0.042). Early PET/CT may predict salvage chemotherapy failure and could inform future clinical trials investigating early therapy change to non-chemotherapy treatments.